Website Based E-Commerce Prototype Design For Packaging Dodol Msmes In Wonosari Village - Titin sumarni; Ivahni; Nur ulfadillah; Zuriatri Putri (Penerbit Hellow Pustaka, 2024)
The development of information and communication technology has had a significant impact on various sectors, including the micro, small and medium enterprise (MSME) sector. In this digital era, the existence of an e-commerce platform is very important to increase the competitiveness of MSMEs, especially in rural areas. One of the superior products that has great potential to be marketed online is packaged dodol, a traditional food that is rich in local taste and culture. The aim of this article is to provide the right solution for business people in marketing their products online. In presenting this article, the author uses qualitative research methods, which are aimed at understanding social phenomena from the participant's point of view or perspective. Participants are people who are interviewed, observed, asked to provide data, opinions, thoughts and perceptions. Based on the results of the discussion, making this application makes it easier for customers to place orders. Make the transaction process easier by utilizing payment via bank transfer.